A Study on Rising Amount of Fake Rape Cases in India - Ms. Asha Rani Rawat, Dr. Ashu Maharshi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The spectre of false allegations of rape also affected considerably the formulation and application of the legal theory. In cases of sexual offences such as corroboration notice, preservation of the domestic harassment immunity, fear of fake claims are used to excuse proof laws to seek to manipulate police and prosecutors' decisions. Sir Matthew Hale's 17th century opinion that rape "is a readily proven and impossible allegation to be defended by the guilty party and that rape complainants, never so innocent, have been prominently portrayed in the judicial response to rape. Many jurisdictions have reflected on how quickly a men can bring harassment accusations and how challenging it is to dispute them. In comparison, the attorneys and the legal experts and academics can use them easily. With the latest 2013 criminal law amendment in India, the possibility of fake rape complaints under the excuse of one or other has increased. The fact is evident from the review of court decisions released by the quick track courts in Delhi and news reports in the media around the world. This increasing hazard, which can harm society's fabric and abuse of law for different purposes, needs to be regulated early. It is perhaps shocking, therefore, that although the problem of false allegations continues to be relevant in handling the treatment of rape by the criminal court system, the credibility of facts surrounding the prevalence of false allegations has not gained much consideration. The present study was designed to contribute another credible estimate of the rate of false rape reporting by using systematic methods to carefully examining a database of 136 cases identified by university students in Delhi.